Estudo da incontinência urinária de esforço e incontinência urinária de urgência em idosas na comunidade - Bevilaqua, Laura Appel (2019)
Urinary incontinence is characterized by involuntary loss of urine and although not inherent in aging, mainly affects women over 65 years. Its consequences can lead to depression, social isolation and other factors that directly affect the quality of life of those affected. When talking about questionnaires for urinary incontinence, most report the impact it promotes on people's lives, but little is said about screening methods to intervene before symptoms worsen. OBJECTIVES: To analyze the presence of stress urinary incontinence and urinary urinary incontinence using the Gaudenz-Fragebogen differential diagnosis instrument in communitydwelling elderly women. METHODS: This is a cross-sectional, analytical, probabilistic study, linked to the institutional research “Comprehensive Care for the Elderly”. To obtain the variables of interest will be used a structured interview, prepared by the researchers that will address the socio-demographic profile and clinical health conditions and the Gaudenz- Fragebogen Instrument. The research protocol will be applied in the home space. The data obtained will be compiled and analyzed using the Statistical Package for Social Sciences (SPSS) (version 22.0). RESULTS: The final sample of this study was 86 women with a mean age of 73.72 ± 8.3 (95% CI 71.9 - 75.5) with a minimum age of 62 and a maximum of 95 years. It was observed that more than half of the elderly women reported involuntary loss of urine, which is more prevalent in stress situations in equal proportion, in emergency situations. More than a third of the elderly experience this situation less than 10 years; and this situation became a problem when losses began. About a quarter of the sample quantifies that urine leaks occur one to four times. Of the elderly women with voiding problems, around 30% use some type of protection to prevent accidents; most use occasionally; and this situation for the elderly is not a cause for social withdrawal. When asked if it was more difficult to control urine by coughing, straining, sneezing, or laughing, most responded in the affirmative; coughing being the most reported in difficulty. Almost 30% of older women report loss when they run, jump or walk. And less than 20% reported that urine loss worsens if sitting or standing still. When asked about whether there is anything that can be done to reduce or prevent accidents, 22.7% of the elderly answered “yes”. However, a percentage of 22.1% answered that they did not know how to reduce or prevent urine leakage; When asked about treatments for UI 18.6% of the elderly reported having been treated for this condition before; of these 8.1% reported success. It was asked about the use of exercises to strengthen the pelvic floor as a treatment measure only 10.5% reported yes. Of the elderly women who answered that they had already tried to perform the exercises, 5.8% answered that they were successful. Of the respondents, 79.1% never had a gynecological surgery; of those who performed 6% was for genital prolapse repair, and 5.9% hysterectomy. With the application of the Gaudenz Fragebogen Instrument, most of the elderly women were classified as SUI. CONCLUSIONS: The Gaudenz-Fragebogen Instrument had limitations, as it only classifies UI between SUI or UI and does not also classify SUI, thus leaving a large number of women found in this study without classification. Further studies with this questionnaire are necessary.